THE CHARACTERISTICS OF EPIDEMIOLOGY, CLINICAL AND PARACLINICAL MANIFESTATION OF CONGETIAL HYPOTHYROIDISM AT NATIONAL CHILDREN’S HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the clinical and subclinical characteristics of children with congenital hypothyroidism at the National Hospital of Pediatrics from January 2015 to January 2020; Subjects: We selected 52 pediatric patients diagnosed with congenital hypothyroidism and inpatient treatment at the National Hospital of Pediatrics from January 2015 to January 2020; Methods: Describe retrospective; Results: Through the study of 52 pediatric patients, we obtained the following results: most children with congenital hypothyroidism can be detected as early as 3 years, even in infancy. A suspected sign of constipation is accompanied by edema, prolonged jaundice, and delayed psychomotor development. Up to 86.5% had THS> 100 µU / ml, 78.8% had an FT3 of 1-2 pg / ml, 73.1% had an FT4 100 µU/ml; FT3 of 1-2 pg/ml; FT4
Keywords: Congenital hypothyroidism, children.